ACCUMULATION OF TRACE METAL ELEMENTS IN SOIL AND IN A VEGETABLE BY FERTILIZER ADDITION - Copaja, Sylvia Violeta; Muñoz, Natalia; Nacaratte, Fallon (Journal of the Chilean Chemical Society, 2025)
The practice of fertilization is necessary to reincorporate and provide the soil with additional sources of nutrients in forms that can be assimilated by plants. Fertilizers often contain very small amounts of trace metals as impurities. These can be incorporated into the human diet through the ingestion of food contaminated with these elements. The soil samples studied came from agricultural soil in the V region, Chile. The characterization carried out indicated a pH and EC expected for a soil with this use, while low values for CEC and MO % were found. The samples were classified as medium P and extremely N-rich soils, and significant increases in these nutrients were found in the SPT and urea treatments, respectively. The soil was incubated according to three different treatments: with 0.1% of urea, superphosphate (SPT) (5.0 g per pot). After 8 weeks of incubation, wheat seed were planted and harvested after three weeks of growth. Trace metals were determined by Atomic Absorption Spectroscopy (AAS). Trace metal concentrations followed the trend: Cu < Cr < Zn < Ni for urea treatment; while: Ni < Cu < Zn < Cr for treatment with SPT. The maximum percentage contributed by fertilization was for Cr (59 %). The concentration of metals in the root, stem and leaf of the crop were found to be below the detection limit, except for Zn and Cu in the root. The bioaccumulation factor for Cu and Zn was less than 1 for all treatments, while the translocation index for Zn was also less than 1. The use of SPT is consistent with a greater contribution of trace metals to the soil compared to urea; consequently, the use of chemical fertilizers could increase the concentration of trace metals in the soil and incorporate them into the vegetables grown in the soil. For this, the use of organic fertilizers such as compost and humus obtained from organic waste raw materials is an increasingly popular alternative in various crops, for which it is necessary to evaluate the trace metal content, as these can accumulate in both the soil and the substrates.